Pectin-based edible coating containing gibberellic acid in the post-harvest conservation of fresh tomatoes - Flores, Karina Sayuri Ueda; Oliveira, Igor Gabriel Silva; de Souza, Vinicius Nelson Barboza; Garcia, Vitor Augusto Dos Santos [UNESP]; Altemio, Ângela Dulce Cavenaghi; Martelli, Silvia Maria (FapUNIFESP (SciELO), 2023)
Edible coating are commonly used as they minimize post-harvest losses and extend the shelf life of fruits. Therefore, in this study, analyzed the effect of edible coatings containing gibberellic acid (GA3 ) on the shelf life of tomatoes (Solanum lycopersicum L.). Tomatoes were divided into six groups: Uncoated (CT); coating with 75 and 100 mg L–1 of GA3 solubilized in water without adding pectin (A75 and A100, respectively); coating with 75 and 100 mg L–1 of GA3 with added pectin (P75 and P100, respectively); coating pectin only (PEC). Pectin-based coatings (PEC, P75, and P100) were produced by solubilizing pectin (3%) in water, followed by adding different concentrations of GA3.Treatments A75 and A100 were prepared with distilled water and 75 and 100 mg L–1 GA3 . Tomatoes (turning stage) were immersed in the solutions for 3 min, dried at room temperature, and stored at 12 °C (90% RH). The pH, titratable acidity, soluble solids, color and weight loss were analyzed every four days for 32 days, and the firmness of the tomatoes was analyzed every seven days for 35 days. Coatings with GA3 maintained firmness, delayed weight loss, and decreased acidity, pH, sugar content, and color changes. Pectin-based coatings (P75, P100) were the most effective in delaying weight loss. The application of GA3 associated with pectin-based coatings delayed the ripening process, maintained the quality, and prolonged the shelf life of fruits. As this is an inexpensive technique, it may be used commercially.
Uso de revestimento comestível à base de pectina contendo ácido giberélico na conservação pós-colheita de tomates frescos
Keywords: Biopolymers; gibberellins; materials technology; shelf life